Exploring Heterogeneity of International Students’ Racial and Native/Non-Native Language Backgrounds in Learning Engagement, Cultural Adjustment, Social Connections from QuantCrit Perspective - Dong, Jianwei; Wang, Chih-Hsuan; Shannon , David (Forum for Linguistic Studies, 2024)
The academic engagement of international students is intricately linked to their diverse social and cultural adjustments in the host culture. However, these aspects have often been investigated from a homogeneous point of view. This study explores the interpersonal characteristics of students from different racial groups and native/ non-native language backgrounds in learning engagement, cultural adjustment, social media use, and social capital. Data were collected using the Qualtrics Survey from 209 international students between November 2021 and May 2022. The results of the MANOVA indicate significant disparities based on their race and native/ non-native language backgrounds within the examined constructs. The findings enrich the body of research through the QuantCrit lens, underscoring that international students are not monolithic. Generalizing their experiences by aggregating various identity group data may fail to capture their complexities. The results revealed that Black students exhibited elevated levels of bridging social capital and learning engagement, potentially linked to increased social media usage. Hispanic students demonstrated lower levels of engagement and socialization. White international students displayed superior cultural adjustment and bonding capital. Conversely, Asian students reported lower levels of learning engagement, cultural adjustment, social media use, and social capital compared to their White, Black, and Hispanic peers. Native language international students outperformed non-native speakers in all assessed areas. The potential reasons for these group differences and administrative support that assists in coping with language, socialization and acculturation challenges are discussed.